2015
DOI: 10.1021/acs.jmedchem.5b01325
|View full text |Cite
|
Sign up to set email alerts
|

Tacrine–Trolox Hybrids: A Novel Class of Centrally Active, Nonhepatotoxic Multi-Target-Directed Ligands Exerting Anticholinesterase and Antioxidant Activities with Low In Vivo Toxicity

Abstract: Coupling of two distinct pharmacophores, tacrine and trolox, endowed with different biological properties, afforded 21 hybrid compounds as novel multifunctional candidates against Alzheimer's disease. Several of them showed improved inhibitory properties toward acetylcholinesterase (AChE) in relation to tacrine. These hybrids also scavenged free radicals. Molecular modeling studies in tandem with kinetic analysis exhibited that these hybrids target both catalytic active site as well as peripheral anionic site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 70 publications
3
87
0
Order By: Relevance
“…6 ), 8d is the best lead molecule from this study as it demonstrated the best ability to inhibit AChE, BuChE and act as a potent antioxidant. This result is supported by recently published work wherein the non-hepatoxicity of tacrine-trolox hybrids has been demonstrated [36]. Novel compound 14 showed promising activity for ChE inhibition and hybrid molecules in this series could also be further explored.…”
Section: Resultssupporting
confidence: 70%
“…6 ), 8d is the best lead molecule from this study as it demonstrated the best ability to inhibit AChE, BuChE and act as a potent antioxidant. This result is supported by recently published work wherein the non-hepatoxicity of tacrine-trolox hybrids has been demonstrated [36]. Novel compound 14 showed promising activity for ChE inhibition and hybrid molecules in this series could also be further explored.…”
Section: Resultssupporting
confidence: 70%
“…Novel multi-target directed ligands (tacrine-pyridine-3-carboxamide hybrids) 1 and 2 were selected upon their IC 50 values (1: hAChE IC 50 = 3.81 ± 2.4 μM; 2: hAChE IC 50 = 0.097 ± 0.009 μM) to confront the multifactorial nature of AD by combining hAChE inhibitor with antioxidant action provided by hydrazinonicotinamide (38)(39). Based on the inhibitory properties, compound 2 was able to increase the therapeutic efficacy of antidotal treatment of acute soman poisoning, while analogue of 7-methoxytacrine (compound 1) is not effective because the potency of 7-methoxytacrine to inhibit AChE is generally much lower compared to tacrine (7-methoxytacrine: hAChE IC 50 = 10.00 ± 1.0 μM; tacrine: hAChE IC 50 = 0.32 ± 0.01 μM) (40). Generally, the tacrine analogues exerting the sufficient prophylactic efficacy due to their potency to reversibly inhibit AChE in the peripheral and central nervous systems are more toxic.…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 value of 6-chlorotacrine was calculated for human AChE and corresponds to 0.2 ± 0.001 µM. It means that 6-chlorotacrine is very strong inhibitor of AChE (37). It is able to increase the resistance of experimental animals against Tab.…”
Section: Discussionmentioning
confidence: 99%